Psychosocial factors related to dietary habits in women undergoing preconception care - Zahra Karami; Nafisehsadat Nekuei; Ashraf Kazemi; Zamzam Paknahad (Wolters Kluwer Medknow Publications, 2018)
Background: Correct health behaviors such as dietary habits before pregnancy ensure desired pregnancy outcomes. The aim of this study was to determine the relationship between psychosocial factors and dietary habits using social cognitive theory (SCT) in women undergoing preconception care (PCC). Materials and Methods: This cross-sectional study was conducted among 120 women from October to December 2015 in health centres in Isfahan, Iran. Using a researcher-made questionnaire, the researcher conducted stratified random sampling and convenience sampling for selecting health centres and participants, respectively. For data analysis, the researcher applied the Pearson, Spearman's, and linear regression test in SPSS software. Results: The results showed that perceived support from healthcare personnel and outcome expectations are not associated with any of the components of dietary habits. Access to healthy food was inversely correlated with incorrect dietary habits (β = −0.19, p = 0.039) and had a direct correlation with daily consumption of fruits (β = 0.27, p = 0.006). Perceived support from the spouse had a direct correlation with desired dietary habits (β = 0.27, p = 0.006). Self-efficacy was inversely correlated with incorrect dietary habits (β = −0.22, p = 0.011) and had a direct relationship with desired dietary habits (β = 0.25, p = 0.004). Conclusions: To improve the nutritional status of women prior to pregnancy, interventions must be focused on increasing women's access to healthy food and their self-efficacy in maintaining a healthy diet.